1985
DOI: 10.1111/j.1545-5300.1985.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Boundary: Family Therapy in a Long‐Term Inpatient Setting

Abstract: The paradigm for inpatient family therapy presented here is intended both as a description of, and a means of thinking about, family therapy in a long-term inpatient setting. It is meant to contribute to a delineation of treatment goals and strategies within a conceptual framework that is rooted in and expresses the complex clinical realities of inpatient treatment, where the locus of family therapy is the family-hospital boundary. The four functions described here are hierarchical in their relationships to ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Some similarities can be seen between our practice and that of others such as Cooklin (1974), Hunter (1985), Hanrahan (1986) and ImberBlack (1988). Our practice seems to differ, however, in the way the treatment team regards itself as being on the boundary.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Some similarities can be seen between our practice and that of others such as Cooklin (1974), Hunter (1985), Hanrahan (1986) and ImberBlack (1988). Our practice seems to differ, however, in the way the treatment team regards itself as being on the boundary.…”
Section: Resultssupporting
confidence: 58%
“…Imber-Black (1988) emphasized the analysis of larger treatment systems in order to avoid the replication of problematic family patterns. Hunter (1985) pointed both to parents' tendencies to displace hostile feelings towards the patient onto the hospital, and to the often considerable resistance on the part of hospital staff to attend adequately to the emotional needs of parents and other members of inpatients' families. He described the family therapist in a long-term inpatient setting as a boundary dweller, a cultural broker whose constant task is to make the hospital and its treatment of the patient intelligible and acceptable to the family and, conversely, to render the family human and comprehensible to the ward staff (Hunter, 1985).…”
Section: The Boundary Of the Hospitalmentioning
confidence: 99%
“…The family may feel overwhelmed by the activity occurring during the initial phase of hospitalization, and the potential for development of negative feelings exists as family roles are restructured (Mandelbaum, 1984). Hunter (1985) suggested that during the initial phase of hospitalization, staff may not attend to the emotional needs of family members and thus may create the potential for negative feelings and conflict. Evidence suggests that it is perceived control over a situation, not actual control, that is important (Kelley, 1967;Langer, 1978).…”
Section: Family Help Not An Easy Taskmentioning
confidence: 99%
“…But, on the other hand, because of the feelings of failure and blame which suffuse the treatment system, staff groups may be induced into partisan bias either for or against the family. This can lead to intense competition between, for instance, parents and staff over the care of a young person (Harbin, 1979;Jones, 1980;Hunter, 1985). These tensions add to the already complex task of adolescent residential treatment with its mixture of high emotional tensions, group dynamics, individual volatility and staff/family transference (Hunter, 1985;Steinberg, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to intense competition between, for instance, parents and staff over the care of a young person (Harbin, 1979;Jones, 1980;Hunter, 1985). These tensions add to the already complex task of adolescent residential treatment with its mixture of high emotional tensions, group dynamics, individual volatility and staff/family transference (Hunter, 1985;Steinberg, 1986). Clearly these factors indicate how crucial a family therapy service is for inpatient units but they also explain why family therapists are wary of providing such a service.…”
Section: Introductionmentioning
confidence: 99%